Co-rotating twin-screw extruder : fundamentals, technology, and applications - Kohlgruber, Klemens (Hanser, 2007)
Co-rotating screws and/or extruders are used in many branches of industry for producing, preparing and/or processing highly viscous materials. They find a wide variety of applications especially in the plastics, rubber and food industries. Co-rotating twin-screw machines usually have modular configurations and are thus quite flexible for adapting to changing tasks and material properties. Well-founded knowledge of machines, processes and material behavior are required in order to design twin-screw extruder for economically successful operations. This book provides basic engineering knowledge regarding twin-screw machines; it lists the most important machine-technical requirements and provides examples based on actual practice. Better understanding of the processes is emphasized as this is a prerequisite for optimizing twin-screw designs and operating them efficiently. Besides basic functions, such as compounding, the book focuses on: - the historical development of twin-screws - the geometry of the screw elements (fundamentals, basic patents, patents overview) - material properties and material behavior in the machine - fundamentals of feed behavior, pressure build-up and power input - examples of applications for various processing tasks - compounding: tasks, applications, processing zones - potential and limits of modeling - scaling-up various processes - machine design incl. drives and materials.